Fluoride-Induced Microhardness Changes in Resin-Modified Glass Ionomer Cements: A Comparative Study - Rufasto-Goche, Katherine Susan (2025)
Background: Resin-modified glass ionomer cement (RM-GIC) is widely used in clinical dental procedures as a restorative material due to its chemical composition. It is known for its strong adhesion to dental structures and its fluoride content. However, fluoride in RM-GIC is insufficient for preventing the formation of carious lesions, making the use of fluoride gel and varnish necessary as preventive strategies. Nevertheless, there may be adverse interactions between RM-GIC and fluoride, which could compromise the properties of these restorative materials. Therefore, it is crucial to understand the physicochemical and biological properties of the products used in dental treatments. This experimental study aimed to evaluate the effect of the following fluorides: 2% neutral sodium fluoride (NaF), 1.23% acidulated phosphate fluoride (APF), and 0.1% fluoride varnish (7700 ppm F) in the mi-crohardness of the RM-GIC. Using GC Fuji II LC-A2, 80 RM-GIC discs measuring 6cm x 4cm were made and immersed in artificial saliva for 7 days. Then, the discs were washed, dried, and randomly divided into 4 groups, and the initial surface microhardness was measured. After that, the discs were immersed in the 3 fluorides to measure the microhardness for a second time. The average value of the surface microhardness of the RM-GIC in the final phase (exposure to fluorides) of the three experimental study groups is lower than the initial phase (non-exposure to fluorides). There was a significant decrease in the microhardness of the ionomer with the application of the three fluorides (p= 3.6x10-12). Particularly, the treatment with 1.23% acidulated phosphate fluoride demonstrated higher variation than 2% neutral sodium fluoride (p=0.0063) or 0.1% fluoride varnish (p=2.2x10-5). In conclusion, 2% neutral sodium fluoride, 1.23% acidulated phosphate fluoride, and 0.1% fluoride varnish (7700 ppm F) applied to RM-GIC decreases surface microhardness.